Far Lateral Approaches: Dural Arteriovenous Fistulae at the Hypoglossal Canal: 3-Dimensional Operative Video. Issue 1 (29th January 2022) - Budohoski, Karol P.; Barone, Damiano G.; Mediratta, Saniya; Ross, Matthew; Kirollos, Ramez W.; Santarius, Thomas; Trivedi, Rikin A.
Abstract : Cognard type V dural arteriovenous fistulae (dAVF) are typically located at the foramen magnum. Their presentation often mimics that of cervical myelopathy, and they can be easily misdiagnosed even if spinal vascular imaging is undertaken. Treatment typically involves endovascular embolization or surgery when embolization is not possible. We describe a case of a 67-yr-old man who presented with progressive symptoms of cervical myelopathy with a significant reduced ambulation and upper motor neuron signs. Imaging disclosed upper cervical cord edema, and angiography confirmed a Cognard type V dAVF with drainage into the perimedullary and spinal venous system. The dAVF was supplied by the hypoglossal division of the ascending pharyngeal artery. Endovascular treatment was believed to pose a risk of ischemic injury to the hypoglossal nerve, and therefore, surgery was offered. Informed consent was obtained. A far lateral approach was used to access the fistulous point. We describe the relevant vascular anatomy and the benefits of the far lateral approach for this lesion. We also demonstrate a tailored inferior condylectomy to gain access to the intracranial part of the hypoglossal canal, where the draining vein is expected to be found. We supplement the discussion with a 3D surgical video.